GENDER INEQUALITY OF WOMEN IN EDUCATION OR WHY WOMEN ARE UNDERREPRESENTED IN LEADERSHIP POSITIONS? - Olga Melnychenko (Неперервна професійна освіта: теорія та практика, 2024)
The article is devoted to one of the main and topical problems of gender studies, namely, gender inequality of women in education when occupying senior management positions. The following categories are understood by the researchers as management positions in higher education institutions: rector, vice-rectors, president, head or director, who acts within the limits of their powers. Despite the fact that education is one of the most feminized branches of Ukrainian society, the heads of the Ministry of Education and Science of Ukraine according to the Soviet tradition were (with a rare exception to the rule) men. The author analyzes gender differences in the distribution of power in the best higher education institutions of Ukraine according to the consolidated rating. Special attention is paid to the state of gender equality in leadership positions at the Borys Grinchenko Kyiv Metropolitan University. The author believes that one of the main tasks of gender is to find out the factors that prevent women from being active and being elected to leadership positions in institutions of higher education. The author believes that one of the main tasks of gender is to find out the factors that prevent women from being active and being elected to leadership positions in institutions of higher education. The article analyzes the scientific literature, in which the following factors are divided into «availability of offers» and «availability of demand»: «availability of offers» includes the potential readiness of women to occupy management positions in higher education institutions; «availability of demand» includes prejudices of educators regarding the leadership of women in the educational sphere, and in institutions of higher education in particular. The author examines the Gender Equality Index of the World Economic Forum, which contains four dimensions related to the subject of the study: economic opportunities for women in leadership positions; the level of women’s education and its quality; the state of women’s health and the possibility of its recovery; the degree of representation of women in leadership positions in the country. The article proposes ways to solve the situation regarding gender inequality of women in leadership positions in higher education institutions of Ukraine. As a way to improve the state of gender inequality of women in leadership positions in higher education institutions of Ukraine, it is proposed to conduct trainings or shortened courses on gender studies for students, teachers, scientists, senior managers of higher education institutions, which will help women believe in themselves, and the management of higher education institutions recognize the possibility of women’s leadership. In the future, it is planned to continue the development of this topic thanks to the analysis of the state of gender equality of women in the management positions of higher education institutions in the European educational environment and its comparison with the Ukrainian one, as well as the search for positive experience and ways to overcome the existing situation.